Sistemática do gênero Trichomycterus Valenciennes, 1832 (Siluriformes : Trichomycteridae) do norte da América Andina - Peixoto, Paula (Universidade do Vale do Rio dos Sinos, 2019)
Fishes of Siluriforms order has the most diversity and Ostariophsi’s distribution, presenting about 5500 species described in the Neotropical Region. The Trichomycteridae family is among the largest catfish families in the Neotropical Region with about 360 valid species in 41 genera and 8 subfamilies. The family forms a monophyletic group with the exception of the Trichomycterinae, which presents taxonomic problems mainly because most of the representatives are located in the Trichomycterus genus, a non-monophyletic group with a considerable richness of approximately 75% of the total family species and possibly a great diversity still unknown. The problematic of the Trichomycterus genus is questioned in several studies, mainly due to the absence of exclusive synapomorphs that make it difficult to study phylogenetic relationships, leading to taxonomic revisions in which some species of Trichomycterus have been redescribed in other genera of the subfamily such as Silvinichthys, Ituglanis, Potamoglanis and Cambeva. In addition, this genus has a very large diversity and distribution (South America) that can lead to the geographic and genetic isolation of certain populations, evidencing non-monophyletic. In this context, our main objective was to study the phylogeny of Trichomycterus of Andean America, with emphasis on the species of Colombia, in order to identify phylogenetic relationships between the cis-andine and trans-andine species from 348 morphological characters. This study also provides the redescription of two Trichomycterus from the Pacific coast of Colombia e Ecuador, Trichomycterus gorgona e Trichomycterus taenia. The study range 49 taxa of which, 38 internal group and 11 external group. The genera used in the external group were Astroblepus, Bullockia, Cambeva, Eremophilus, Hatcheria, Ituglanis, Scleronema and Silvinichthys. Morphometry and meristic of the specimens were carried out, surveying 348 morphological characters that were compiled from the works of DoNascimiento (2013), Baskin (1973), de Pinna (1992, 1988, 1989, 1998), Arratia (1990), Costa & Bockmann (1994) and Katz et al,. (2018) and used for the first time in this work with inner group species followed by a phylogenetic analysis for the interpretation of cladograms and relationships between Cisandine and Transandine species. Trichomycterus polyphylism remained in our results. We also identified that Trichomycterus stricto sensu is restricted to the southeastern region of Brazil and, therefore, the Transandine species belong to a genus not yet described. The relationship of Trichomycterus stricto sensu as Cambeva's sister group was corroborated in this work as well as the monophily of the Cambeva genus and the relations between Scleronema and Ituglanis.
Keywords: Anatomia; Colômbia; Filogenia; Redescrição; Trichomycterinae; Anatomy; Colombia; Phylogeny; Redescription; Trichomycterinae; ACCNPQ::Ciências Biológicas::Biologia Geral